A Contextual Approach to Resources in Smart Home Care Environments - Dornelles, Lorayne Pinheiro; Moraes Neto, Moacyr Franco de; Wives, Leandro Krug (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2017: Anais Estendidos do XXIII Simpósio Brasileiro de Sistemas Multimídia e Web, 2017)
Currently, with the popularization and maturation of the Web, the Internet is seen as a service platform, and the physical objects used in daily life start earning computational capacity. This objects become addressable and are used to identify and provide information on the web for the environment to which they are inserted. In this context, the paper presents a model that uses IoT concepts for notification of resource state changes and the integration of services into Home Care Smart Environments.